STOCK ESTIMATION OF BAUNG FISH (Hemibagrus nemurus) IN THE INDRAGIRI RIVER, LUBUK VILLAGE, ABOUT GUNUNG TOAR DISTRICT, KUANTAN SINGINGI REGENCY, RIAU PROVINCE - Ramadhan, Wahyu; Sumiarsih, Eni; Fauzi, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTLubuk Terentang Village is one located near Indragiri River, Riau Province. Indragiri river is a habitat for several types of fish, one of which is the baung fish (Hemibagrus nemurus). The population of baung fish in the river is threatened due to former mining in the upstream area of the Indragiri River. This study was conducted to determine the stock of baung fish population at a certain time. The population of baung fish stock was calculated through the estimation of the area emptying method or the Depletion Methods. The results showed that the initial population (No) of baung fish (H. nemurus) in the Indragiri River, Lubuk Terentang Village in August 2020 was 836 kg and the final population (Nt) was 798 kg. The maximum value of baung fish that can be exploited is 418 kg per month, and the optimal effort is 14 units of net.Keywords:Catfish,Depletion Methods,Fish stock, Hemibagrus nemurus, Indragiri River